Pengaruh Peran Kepala Sekolah, Profesionalisme Guru, Dan Partisipasi Masyarakat Terhadap Peningkatan Mutu Pendidikan - Purtiningsih, Okta; Nurkolis, Nurkolis; Kusumaningsih, Widya (Jurnal Inovasi Pembelajaran di Sekolah, 2024)
This study aims to describe and analyze: Improving the Quality of Education in KKG Kartini, Brebes Regency (1) The Influence of the Principal's Role on the Quality of Education (2) The Influence of Teacher Professionalism on the Quality of Education (3) The Influence of Community Participation on the Quality of Education (4) The Influence of the Principal's Role, Teacher Professionalism and Community Participation on Improving the Quality of Education in KKG Kartini, Brebes Regency. The background of this study is the fact that the Quality of Education in KKG Kartini, Brebes Regency is low. Academic Supervision is rarely carried out and Teacher Professionalism and Community Participation are factors that influence the improvement of the Quality of Education. This study uses a quantitative research approach and an ex post facto research type. The population of the study was all public elementary school teachers in KKG Kartini, Brebes Regency, totaling 108 teachers in 9 public elementary schools with a research sample of 30 teachers. The analysis of this study includes normality test analysis, linearity test, multicollinearity test, and homogeneity test. Hypothesis testing includes simple regression test and multiple regression test with α = 0.05. The results of the study indicate that: (1) there is an influence of the principal's role on the quality of education as stated by the simple regression equation Ŷ = 19.511 + 0.898X1, with a contribution of 91.5%; (2) there is an influence of teacher professionalism on the quality of education as stated by the simple regression equation Ŷ = 45.111 + 0.757X2, with a contribution of 79.1%; (3) there is an influence of community participation on the quality of education stated by the simple regression equation Ŷ = 37.558 + 0.801X3 with a contribution of 84.1% and (4) there is an influence of the role of the principal, teacher professionalism and community participation on the quality of education stated by the multiple regression equation Ŷ = 19.310 + 0.714 X1 + -0.149 X2 + 0.335 X3 with a contribution of 92.4%. The researcher's suggestions are: (1) prepare a budget for teacher development in order to improve the quality of education; (2) the principal should always try to create his role to always motivate teachers in working so that it will affect the increasing quality of education; and (3) teachers develop themselves by taking training and learning according to their expertise.